Reducing uncertainty in estimating associations of oral exposures with Helicobacter pylori serology in the general population. (27th July 2018) - Schwahn, Christian; Samietz, Stefanie; Mundt, Torsten; Völzke, Henry; Kocher, Thomas; Mayerle, Julia; Holtfreter, Birte; Lerch, Markus M.; Biffar, Reiner; Schulz, Christian
Abstract: Aim: Evidence for reducing Helicobacter (H.) pylori by periodontal therapy comes from small studies in China, limiting generalizability. To estimate the association between periodontal disease and anti‐ H. pylori IgG titer levels in a European country, we used population‐based data from the Study of Health in Pomerania. Materials and Methods: For pocket depth as the primary exposure, we restricted the age range to participants younger than 60 years ( n = 2, 481) to avoid selection bias due to edentulism in this cross‐sectional study. For the full age range up to 81 years, we chose the number of missing teeth ( n = 3, 705). Results: The association between pocket depth and the outcome was weak. Given the ceiling effect for the number of missing teeth (ordinal logistic regression; odds ratio of the interquartile range effect = 1.6; 95% CI: 1.3–1.9; p ‐value for linearity = 0.005), we checked whether wearing removable dental prosthesis was associated with higher anti‐ H. pylori IgG titer levels (odds ratio = 1.3; 95% CI: 1.1–1.5). Conclusions: Tooth loss and wearing removable dental prosthesis were weakly to moderately associated with higher anti‐ H. pylori IgG titer levels in the general population of a European country.